Assessment of the viability of using saline reclaimed water in grapefruit in medium to long term - Romero-Trigueros, Cristina; Nortes, Pedro A.; Pedrero, Francisco; Mounzer, Oussama; Alarcón, Juan J.; Bayona, Jose M.; Nicolás, Emilio (Spanish Journal of Agricultural Research, 2014)
Citrus trees are strongly affected by salinity, especially in countries where irrigation is required as a semi-arid Mediterranean agronomic region. The aims of the study were i) to identify the best reliable plant-based water status indicator for field grown grapefruit trees irrigated with saline reclaimed water during five years of cultivation by measuring seasonal changes in physiological parameters (i.e. gas exchange and stem water potential measurements), leaf structural traits (i.e. leaf chlorophyll content, area-based leaf nitrogen and area-based dry mass), phytotoxic elements and yield; ii) to estimate phytotoxicity thresholds at leaf level. Our results showed that the chlorophyll content was the parameter with the highest number of measures with significant differences (p≤0.05, ANOVA) between trees irrigated with reclaimed water and control trees throughout growing stages. Moreover, Chl a increased linearly with area-based leaf nitrogen (R2=0.63; p<0.001) and area-based dry mass (R2=0.64; p<0.001). We also determined the salt-induced phytotoxicity thresholds at which a reduction in yields occurs; these levels were Na: 0.1 g/100 g, Cl: 0.6 g/100 gand B: 100 ppm. In conclusion, we revealed the importance of leaf chlorophyll measurements as a significance diagnostic indicator of salt stress on field grown grapefruit trees. This parameter was also related to plant-based water status indicators such as stem water potential, stomatal conductance and net photosynthesis. Additionally, a salt accumulation potential at leaf level was shown, leading to possible risk in crop sustainability in the medium to long term.